Percepções sobre a cultura organizacional: um estudo de caso na empresa I - Avila, Denise (Universidade do Vale do Rio dos Sinos, 2013)
In a business world, the phenomenon of globalization shortened barriers and brought to the fore the need for a solid framework for the maintenance of the companies. For the construction of this structure aiming organizational growth, it is important that companies allow themselves to know and analyze their organizational culture, as well as reflect on aspects aimed at defining elements relevant to its direction, like their mission, vision and values, the structure for a strategic planning. This work proposes a study on a young company that is engaged in the development and import of products for personal care, were the objective is to analyze the main perceptions of managers and director regarding the organization were they act, which may contribute to the knowledge of the organizational culture and the future consideration of the company’s strategic planning. For this study we performed a case study using qualitative research, through interviews with the company’s director, and quantitative, with the application of questionnaires to managers.
Keywords: Cultura organizacional; Planejamento estratégico; Percepções; Organizational culture; Strategic planning; Perceptions